2009
DOI: 10.1249/mss.0b013e3181a61495
|View full text |Cite
|
Sign up to set email alerts
|

Physically Active Academic Lessons and Time on Task

Abstract: Physically active classroom lessons provide a buffer to prevent the steep reduction in TOT experienced after a period of inactivity in all children, especially those who are overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
168
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(193 citation statements)
references
References 16 publications
17
168
2
5
Order By: Relevance
“…Öğrencile-rin okula devamı ve konsantrasyonu artar ve sağlığı geliştirme davranışlarının benimsenmesi kolaylaşır (CDC 2012b). Çünkü fiziksel aktivitenin sınıf içi görev davranışını etkileyerek başarıyı artırdığı ve fiziksel aktivitenin daha iyi sınıf içi davranışlarla ilişkisi olduğu gösterilmiştir (Siedentop 2009, Grieco et al 2009. Bunun yanısıra akademik müfredat içine ilave edilen haftada 3 kez olmak üzere, günlük 30 dakika fiziksel aktivitenin akıcı zekâyı (hızlı ve kısa sonuca ulaşabilme) artırdığı ve sosyal çalışmaların başarı testlerindeki performansı geliştirdiği belirlenmiştir (Reed et al 2010).…”
Section: Benlik Saygısı Ruh Hali Ve Psikolojik İyilik Hali üZerine Eunclassified
“…Öğrencile-rin okula devamı ve konsantrasyonu artar ve sağlığı geliştirme davranışlarının benimsenmesi kolaylaşır (CDC 2012b). Çünkü fiziksel aktivitenin sınıf içi görev davranışını etkileyerek başarıyı artırdığı ve fiziksel aktivitenin daha iyi sınıf içi davranışlarla ilişkisi olduğu gösterilmiştir (Siedentop 2009, Grieco et al 2009. Bunun yanısıra akademik müfredat içine ilave edilen haftada 3 kez olmak üzere, günlük 30 dakika fiziksel aktivitenin akıcı zekâyı (hızlı ve kısa sonuca ulaşabilme) artırdığı ve sosyal çalışmaların başarı testlerindeki performansı geliştirdiği belirlenmiştir (Reed et al 2010).…”
Section: Benlik Saygısı Ruh Hali Ve Psikolojik İyilik Hali üZerine Eunclassified
“…This is supported by empirical research, [3][4] [5][6] [7] etc. research demonstrates that physical education and physical activity help learners to learn actively, efficiently and interestingly by helping the learning mechanism.…”
Section: Introductionmentioning
confidence: 68%
“…A handful studies have examined the impact of classroombased PA breaks on attention and concentration quantitatively and qualitatively [3,[19][20][21][22][23][24][25][26][27][28]. The studies have shown that the classroom-based PA can improve children's attention and concentration [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The studies have shown that the classroom-based PA can improve children's attention and concentration [19][20][21][22][23][24]. In a study of implementing daily 10-minute physically active academic lessons (Energizers) to 62 third-and four-grade students for 12 weeks, Mahar et al [23] found significant increases in on-task behaviors (i.e., appropriate verbal or motor behaviors) from pre-Energizers treatment to post-Energizers treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation